The serpent's secret - DasGupta, Sayantani; To, Vivienne (New York : Scholastic Press, 2018)
Up until her twelfth birthday, Kiranmala considered herself an ordinary sixth-grader in Parsippany, New Jersey, but then her parents disappear and a drooling rakkhosh demon shows up in her kitchen, and soon she is swept into another dimension, full of magic, winged horses, talking birds (very annoying), and cute princes--and somehow Kiranmala needs to sort it all out, find her parents, and basically save the world.
School Library Journal starred, January 2018
Booklist starred, November 2017
Publisher's Weekly, December 2017
Bulletin (Center for Children's books), February 2018
Kirkus Review, November 2017
Library Media Connection, January 2018
Keywords: Missing persons -- Fiction; East Indian Americans -- Fiction; Princesses -- Fiction; Magic -- Fiction; Quests (Expeditions) -- Fiction; Fantasy fiction; Action and adventure fiction